ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM KEPUTUSAN PEMBELIAN PRODUK KEK PISANG VILLA KOTA BATAM - Rini Mayangsari; Rusda Irawati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This study aims to determine what factors are taken into consideration consumers in product purchasing decisions Kek Pisang Villa Batam. Technique data collection using questionnaires and documentation. Methods of data analysis used in this research is descriptive analysis and confirmatory factor analysis (CFA). The results showed that of the 20 indicators analyzed, can form six new factors namely factor Product Quality, Brand Image, Product Pricing, Form of Packaging, Competitors and Quality Packaging. While most dominant factor consumers consider the product purchasing decisions Kek Pisang Villa is a factor Quality Products with a value of 24 322% variance.